Text on front in Dutch: 'Bayrut, March 16 [1977]. Kamal Djoemblat, leader of the Druzen and founder of the progressive socialist party in Libanon. He was killed Wednesday in an embus 50 kilometers south-east of Bayrut. By the assault in Douri Kfarin his bodyguard and driver were also killed
Text on front in Dutch: 'Bayrut, March 16 [1977]. Kamal Djoemblat, leader of the Druzen and founder of the progressive socialist party in Libanon. He was killed Wednesday in an embus 50 kilometers south-east of Bayrut. By the assault in Douri Kfarin his bodyguard and driver were also killed.